Legal Analysis of Corporate Insolvency: A Case Study of the Insolvency Resolution Process - Zairi Absi, Warmiyana; Utoyo, Marsudi (International Journal of Social Service and Research, 2023)
Bankruptcy is a situation that can be experienced by all who run their business, bankruptcy is a debtor who is in an unfavorable state because all his assets are not enough to meet his needs to pay all his debts. So that legal problems arise when a company experiences financial difficulties, in Indonesia bankruptcy law is regulated in Law number 37 of 2004. The purpose of the study is to analyze bankruptcy law, especially the bankruptcy settlement process. The research method used in this study is the descriptive qualitative method. Data collection is carried out through literature studies (library research), then the collected data is analyzed through three stages, namely data reduction, data presentation, and conclusions. The results showed that Law Number 37 of 2004 can provide legal protection to creditors, debtors, and the public fairly and equitably. The bankruptcy settlement process can be carried out through two stages, namely the PKPU stage or postponement of debt payment obligations and the bankruptcy settlement process. The bankruptcy settlement process consists of several stages, namely the first bankruptcy application, the examination of the bankruptcy application, the bankruptcy statement decision, the appointment of a receiver, the distribution of debtor's assets, and then the last stage of the bankruptcy closing decision.